2011
DOI: 10.1007/s00253-011-3399-8
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mixotrophy on microalgal growth, lipid content, and expression levels of three pathway genes in Chlorella sorokiniana

Abstract: Nannochloropsis oculata CCMP 525, Dunaliella salina FACHB 435, and Chlorella sorokiniana CCTCC M209220 were compared in mixotrophic and photoautotrophic cultures in terms of growth rate, protein, and lipid content. Growth improved in glucose, and the biomass productivities of N. oculata, D. salina, and C. sorokiniana were found to be 1.4-, 2.2- and 4.2-fold that observed photoautotrophically. However, biomass and lipid production decreased at the highest glucose concentrations. Meanwhile, the content of protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
108
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 265 publications
(123 citation statements)
references
References 34 publications
13
108
0
2
Order By: Relevance
“…However, the alga culturing in strict heterotrophy is more expensive than in photoautotrophy. Mixotrophic cultivation is not only complement photoautotrophy with organ carbon, but also can reduce the cost of heterotrophic microalgal culture and improve the lipid content (Wan et al 2011). Hence, the microalga cultured under mixotrophic condition can exhibit higher biomass and lipid content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the alga culturing in strict heterotrophy is more expensive than in photoautotrophy. Mixotrophic cultivation is not only complement photoautotrophy with organ carbon, but also can reduce the cost of heterotrophic microalgal culture and improve the lipid content (Wan et al 2011). Hence, the microalga cultured under mixotrophic condition can exhibit higher biomass and lipid content.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Chlorella is the oldest commercial application of microalgae and can be grown in photo/mixo/heterotrophic mode of culture. C. sorokiniana is a promising freshwater non-motile unicellular alga, accumulating high amounts of lipids and proteins (Wan et al 2011). C. sorokiniana is one of potential microalgal species used for the lipid production.…”
Section: Introductionmentioning
confidence: 99%
“…The transcription of the four genes appears to be coordinated, and maybe the level of accD subunit is a determinant of ACCase level (Madoka et al, 2002;Ke et al, 2000), so the transcription abundance of accD gene can reflect the response of ACCase to changing culture conditions. Since it is considered to be very important in regulating fatty acid and thus oil biosynthesis, the genetics of ACCase has been well studied in many plants; as for oleaginous microalgae, only Wan et al (2011) reported recently in C. sorokiniana that increased lipid contents in stationary phases of mixotrophic growth were related to increased expression levels of accD gene. Our results showed that the expression levels of accD gene began to increase during the exponential phases under heterotrophic cultivations, but elevated expression of this gene did not lead to elevation of lipid contents in the same degree as in the stationary phases.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported in another algal species Chlorella sorokiniana that increased expression levels of accD (heteromeric acetylCoA carboxylase beta subunit) might account for the increased lipid content in stationary phase of mixotrophic growth (Wan et al, 2011). The species in the genus Chlorella are usually from different circumstances, and the same metabolic pathways in two species often response differently to the same environmental condition (Cha et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…В силу различных свойств белковых соединений именно они обусловливают многообразие ответных реакций водорослей на различные воздействия. Известно, что в условиях выращивания водорослей в миксотрофной и автотрофной культурах можно получить биомассу с совершенно разным выходом белка, аминокислот, каротиноидов, липидов и других важных соединений (Wan et al, 2011).…”
Section: результаты и обсуждениеunclassified